AB1247-HPR Interprofessional Bio-Psycho-Social Rehabilitation and Its Effects on Suffering and Occupational Performance – An Observational Study of a Cohort of 92 Chronic Pain Patients. (9th June 2015) - Heigl, F.; Schärer, P.; Widmer Leu, C.; Winteler, B.; Bachmann, S.; Caliezi, G.; Reichenbach, S.; Villiger, P.M.
Abstract : Background: Chronic musculo-skeletal diseases cause high direct and indirect costs. Chronic pain remains a challenge in clinical practice. Effectiveness of interprofessional bio-psycho-social rehabilitation programs in an outpatient setting needs to be shown 1, 2 . Objectives: To evaluate the mid- and long-term effects of an interprofessional outpatient program on the outcomes: Suffering (Self-Illness-Separation), subjective occupational performance and satisfaction, and observed occupational performance. Methods: In this observational study we analyzed systematically 92 chronic pain patients (mean age =44, SD 12, with different diagnoses including non-specific low back pain and fibromyalgia). Assessments were performed pre, within (post intensive phase after 4 weeks) and post program (after 12 weeks), and after 12 months (46 patients). The intervention consists of a multimodal 12 week program (4 week intensive standard phase, followed by an 8 week individualized phase to stabilize and consolidate) including group settings (medical training, Nordic walking, psychology, leisure and ergonomics) and one to one occupational therapy including workplace visits, physiotherapy, psychology, social work, medical care, managing sleep and nutrition problems. The outcomes were evaluated with the COPM (Canadian Occupational Performance Measure), the AMPS (Assessment of Motor and Process Skills), and the PRISM (Pictural Representation of Illness and Self Measure). Descriptive statistical analysis was performed using an intention-to-treat approach with the last available data. Results: All outcomes show a clinical relevant improvement in mean after 4 and 12 weeks, respectively. 1-year-follow-up shows an additional improvement in all outcomes except ADL process skills. Conclusions: This 12-week multimodal bio-psycho-social outpatient rehabilitation program leads to a lasting improvement in occupational performance (subjective and observed) and reduction in suffering caused by chronic pain. The ongoing improvement over 1 year strongly suggests behavioral changes of the participants, leading to better muscular fitness and improved coping strategies. References: Airaksinen O, Brox JI, Cedraschi C, Hildebrandt J, Klaber-Moffett J, Kovacs F, Mannion AF, Reis S, Staal JB, Ursin H, Zanoli G: Chapter 4: European guidelines for the management of chronic nonspecific low back pain. Eur Spine J 2006, 15(Suppl 2):S192-S300. Scottish Intercollegiate Guidelines Network (SIGN). Management of chronic pain. Edinburgh: SIGN; 2013. http://www.sign.ac.uk . Disclosure of Interest: None declared